Examining the impact of rehabilitation interventions on quality of life (QoL) in people with amyotrophic lateral sclerosis (ALS) - Soofi, Ammarah Yasmin (My University, 2016)
The purpose of this thesis is to examine how rehabilitation interventions, specifically physiotherapy (PT), occupational therapy (OT), and speech and language pathology (SLP) or a combination of these interventions affect quality of life (QoL) in people with amyotrophic lateral sclerosis (ALS). The purpose of the first study (Chapter 2) was to synthesize qualitative research through a qualitative meta-synthesis on the potential of rehabilitation interventions to maintain and/or improve QoL from the perspective of people with ALS. The literature search for this study was conducted using the SPIDER strategy and five articles were included. Four themes emerged: 1) the concept of control; 2) adapting interventions to disease stage; 3) struggles with interventions; and 4) barriers between healthcare providers and patients. The evidence suggests that from the perspective of people with ALS, PT, OT, and SLP interventions, or a combination of these interventions have the potential to be beneficial in the management of people with ALS and to optimize QoL. The systematic review (Chapter 3) aimed to determine the effectiveness of rehabilitation interventions, in particular PT, OT and SLP interventions or a combination of these interventions, on QoL in people with ALS. The PICO search strategy was used and six studies were included: three RCTs, two cohort studies, and one cross-sectional study. A narrative synthesis of interventions was conducted as the included studies were not sufficiently similar thus data extracted were not adequate for conducting meta-analyses. Need to briefly discuss interventions, which outcomes you included and inconsistency in results across studies. Due to the limited evidence, it was difficult to determine the exact effects of the interventions from each rehabilitation field to affect QoL for people with ALS. The evidence suggests that more research is required; currently therapists need to rely on their clinical expertise, expert opinions, and theoretical models to select the most effective interventions to sustain or improve QoL in people with ALS. Future research needs to take into consideration the needs of people with ALS to evaluate the impact of rehabilitation interventions on QoL.
Keywords: amyotrophic lateral sclerosis; rehabilitation; quality of life